Simultaneous TESS and NGTS transit observations of WASP-166 b. Issue 4 (24th April 2020) - Bryant, Edward M; Bayliss, Daniel; McCormac, James; Wheatley, Peter J; Acton, Jack S; Anderson, David R; Armstrong, David J; Bouchy, François; Belardi, Claudia; Burleigh, Matthew R; Tilbrook, Rosie H; Casewell, Sarah L; et al.
ABSTRACT: We observed a transit of WASP-166 b using nine Next Generation Transit Survey (NGTS) telescopes simultaneously with the Transiting Exoplanet Survey Satellite (TESS) observations of the same transit. We achieved a photometric precision of 152 ppm per 30 min with the nine NGTS telescopes combined, matching the precision reached by TESS for the transit event around this bright ( T  = 8.87) star. The individual NGTS light-curve noise is found to be dominated by scintillation noise and appears free from any time-correlated noise or any correlation between telescope systems. We fit the NGTS data for T C and R p / R * . We find T C to be consistent to within 0.25σ of the result from the TESS data, and the difference between the TESS and NGTS measured R p / R * values is 0.9σ. This experiment shows that multitelescope NGTS photometry can match the precision of TESS for bright stars, and will be a valuable tool in refining the radii and ephemerides for bright TESS candidates and planets. The transit timing achieved will also enable NGTS to measure significant transit timing variations in multiplanet systems.